Long-Term Destiny of Corneal Endothelial Cells in Anterior Chamber Intraocular Lens-Implanted Eyes. (24th December 2020) - Tang, Yating; Xu, Jie; Chen, Jiahui; Lu, Yi
Abstract : Purpose . To investigate the long-term changes of corneal endothelial cells (EC) in anterior chamber intraocular lens- (AC-IOL-) implanted eyes. Methods . Retrospective study. We included 37 eyes (25 patients) that received AC-IOL implantation previously in the Eye and ENT Hospital of Fudan University between 1995 and 2016. Follow-up outcomes included the best-corrected visual acuity (BCVA), endothelial cell density, hexagonality, coefficient of variance, and central corneal thickness. Results . In total, 23 eyes (62.16%) with phakic and 14 eyes (37.84%) with aphakic AC-IOLs were included. Among these, 3 eyes (8.11%) were angle-supported AC-IOLs and 34 eyes (91.89%) were Artisan iris-fixated AC-IOLs. The mean age of patients was 41.40 ± 17.17 years, and the mean follow-up time was 12.12 ± 4.71 years in our study. At the follow-up time, corneal decompensation existed in 3 angle-supported AC-IOL eyes with a rate of 100% and 15 iris-fixated AC-IOL eyes with a rate of 44.12%. AC-IOL displacement occurred in 14 (41.18%) iris-fixated AC-IOL eyes. In the 19 iris-fixated AC-IOL eyes without corneal decompensation, significant changes also took place in corneal endothelial cells. The endothelial cell density decreased from 2843.26 ± 300.76 to 2015.58 ± 567.99 cells/mm 2 (29.1% loss, P < 0.001 ) and hexagonality decreased from 51.21 ± 7.83 to 42.53 ± 9.17 (%) (16.9% loss, P < 0.001 ). The Kaplan–Meier survival curve also demonstrated the accumulated expectation rates of corneal endothelial cell decomposition for AC-IOLs with a median survival time of 12 years. Conclusion . We reported a significant chronic loss and long-term decompensation destiny of corneal endothelial cells in AC-IOL eyes. Semiannual or annual follow-up and evaluation of endothelial cells should be conducted in AC-IOL-implanted patients.